PERTUMBUHAN BERBAGAI KLON TANAMAN TEBU (Saccharum officinarum L.) DI KEBUN JUWET DUKUHDIMORO, MOJOAGUNG – JOMBANG - Siti Nurazizah; Setyo Budi; Wiharyanti Nur Lailiyah (Agroplantae: Jurnal Ilmiah Terapan Budidaya dan Pengelolaan Tanaman Pertanian dan Perkebunan, 2022)
Sugar productivity in 2015-2019 has decreased because the varieties used have genetic degradation, resulting in decreased growth and productivity. The aim of the study was to determine the genetic diversity and growth of sugarcane (Saccharum officinarum L.) in clones SB01, SB03, SB04, SB11, SB12, SB19, and SB20. The research was conducted in the garden of the Sugarcane Research and Development Center (P3T) PG Gempolkrep PT Perkebunan Nusantara X (PTPN X) Dukuhdimoro Village, Mojoagung District, Jombang Regency in February – April 2022. The materials tested were clones SB01, SB03, SB04, SB11 , SB12, SB19, SB20, BL and PS881 varieties. The variables observed comprised an increase in stem height, increase in stem diameter, number of stems, number of leaves, and leaf area. Data analysis using ANOVA, BNT test, genetic diversity, heritability and genetic progress. The results of the study show SB 12 clone had the best growth, including the increase in stem height of 103.80; the number of bars 4.17 (WAT) and 5.00 (33 WAT); leaf area of ​​646.08 cm2 (31 WAT) and 52.67 cm2 (33 WAT). Heritability values for increasing stem height (129.08) and leaf area (1546.79). The value of genetic progress (239.85) and leaf area (3035.64). So, the selection of the growth character is effective.